Fluks Co2 Pada Berbagai Kondisi Hutan Rawa Gambut Di Areal Konsesi PT. Diamond Raya Timber Kecamatan Bangko Kabupaten Rokan Hilir - Sarigiar Tono; Wawan2 '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was titled CO2 flux in various conditions of peat swamp forest in the concession area of PT. Diamond Raya Timber districtBangko of Rokan Hilir.CO2 flux is the amount of carbon dioxide of gas released by the plants, either from the air or from the plant into the air as a certain expansion of the plant per unit time. Peat swamp forest is a natural resource in which is very important, one of the benefits is which it can control and absorb carbon dioxide in the air. The Factors which affect the release of CO2 into the air flux is microclimate including air temperature , soil temperature and moisture . The purpose of this study was to be determined the amount of CO2 emitted flux on various conditions including peat swamp forests, undisturbed forest, logged and vacant land. This research has been done using purposive random sampling method. These results indicate that the average CO2 flux on peat swamp forests are still natural (intact) is smaller than the logged peat swamp forest and vacant land. As the result general there is no correlation between soil temperature and humidity on the release of CO2 flux that undisturbed forest , in the logged and vacant land. CO2 flux in undisturbed forest and logged derived from plant respiration and activity of soil biota , while the vacant land CO2 fluxes derived from the respiration of soil biota. Keyword : peat swamp forest, micro-climate, CO2 flux